LITERATUR REVIEW: DESTINATION IMAGE AND REVISIT INTENTION - Mahardika, I Made Ngurah Oka (Waisya : Jurnal Ekonomi Hindu, 2024)
In the rapidly growing tourism industry, destination image plays a key role in influencing tourists' intention to revisit a place. This article outlines the relationship between destination image, experience, satisfaction, and intention to revisit. A positive destination image can shape tourists' satisfying experiences, which in turn increases their level of satisfaction and encourages the intention to return. Positive experiences during previous visits strengthen the desire to revisit the destination. Tourist satisfaction becomes a key factor in forming the intention to revisit, as it reflects the fulfillment of their expectations regarding the services and facilities provided. The article also outlines strategies that destination managers can take to enhance tourists' experiences and satisfaction, including improving service quality, interaction with local residents, and sustainable innovation. By understanding this relationship, destination managers can build a good reputation and create unique experiences for tourists, driving the growth and sustainability of the tourism industry.